2014
DOI: 10.3989/scimar.04091.27b
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and functional histochemistry of the digestive and visual systems and other organs during the larval development of the thick-lipped grey mullet, <em>Chelon labrosus</em>

Abstract: Summary:The main ontogenetic and functional changes of the digestive and visual systems of Chelon labrosus during the first three months from fertilization until 99 days post-hatch (dph) are described. An extended slow growth pattern (3.93%) during the first three weeks of larval life was discernible. A long transitional period of mixed endo-exogenous feeding was noticeable until 13 dph. The majority of organ systems and structures (eye, digestive system, liver, pancreas, thyroid and others) were developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 53 publications
8
17
1
Order By: Relevance
“…In this regard, it can be concluded that growth processes in C. labrosus are influenced by stocking density depending on the age of the specimens. In addition, different patterns of body mass increase have been previously demonstrated in larvae and early juveniles of this species from hatching to 99 dph attending to age and developmental ontogenetic changes (Sarasquete et al, 2014). Moreover, growth rates did not show alterations related to the culture conditions in any of the periods analyzed in this experiment, but they are influenced by the age period during which the stress source (stocking density) is applied.…”
Section: Tablementioning
confidence: 74%
“…In this regard, it can be concluded that growth processes in C. labrosus are influenced by stocking density depending on the age of the specimens. In addition, different patterns of body mass increase have been previously demonstrated in larvae and early juveniles of this species from hatching to 99 dph attending to age and developmental ontogenetic changes (Sarasquete et al, 2014). Moreover, growth rates did not show alterations related to the culture conditions in any of the periods analyzed in this experiment, but they are influenced by the age period during which the stress source (stocking density) is applied.…”
Section: Tablementioning
confidence: 74%
“…A reduced initial growth in early H. guttulatus life stages is related to the simplicity of their gut anatomy, which develops with age from a short and straight tube into a long and segmented duct. The presence of acidophilic granules and supranuclear vacuoles in the intestine has been described in larvae of many species (Boulhic & Gabaudan, ; Gisbert et al ., ; Hachero‐Cruzado et al ., ; Luizi et al ., ; Park et al ., ; Sarasquete et al ., ; Yúfera et al ., ), resulting from protein pinocytotic uptake and lipid accumulation before stomach development and lipid metabolism becomes functional (Gisbert et al ., ; Izquierdo et al ., ). Protein absorption in larval stages is faster in the posterior intestine.…”
Section: Discussionmentioning
confidence: 97%
“…Oesophageal goblet cells are directly linked to the ability of fish larvae to start exogenous feeding, improving food ingestion. They play an important role lubricating and protecting the digestive mucosa from chemical and physical damages, thus facilitating the transit of food (Sarasquete et al ., ; Sarasquete et al .,). Moreover, goblet cells take part in physiological processes such as nutrient absorption, antimicrobial function, binding of hormones and protection of cells from phagocytosis and dehydration (Bansil & Turner, ; Díaz et al ., ; Domeneghini et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the current archaeal primers could amplify the archaeal 16S rRNA gene from gut contents of only adults. Generally, archaea have been recorded in the guts of adult fishes, as natural fermenters of indigested food remnants, while fingerlings have incomplete gut, and consequently, may lack the favorite conditions for growth of archaea [22]. Other possibility for negative detection of archaea in fingerling guts may refer to the efficiency of the current primers.…”
Section: Resultsmentioning
confidence: 99%